Development of online media based on the KIK-IRMA learning model on learning to write criticism and essays in the Indonesian language and literature education study program, Jambi University - Irma Suryani; Rasdawita Rasdawita; Liza Septa Wilyanti; Priyanto Priyanto (Universitas Ahmad Dahlan, 2022)
The purpose of this development research is to develop online media in learning to write criticism and essays in universities. The results of observations on students' ability to write literary criticism are still low. Based on this, it is necessary to develop and design instructional media that complement the course of writing criticism and essays. The research and development that the author will do is using the ADDIE method with the KIK─IRMA model step. The results and conclusions of the study are: 1) based on expert validation, it is concluded that the media writing criticism and essays in terms of material, media and language is very valid, so that the media can be used. 2) based on the student assessment, the developed media is classified as practical, so that the media can be used, 3) After it is declared fit for the trial, the media is then tested using the KIK─IRMA model step on an individual scale and on a field scale. After the individual and field trials were completed, the level of effectiveness and practicality was obtained. Based on the results of the pretest and posttest cognitive, psychomotor, and affective aspects of this learning media are classified as effective and practical to use.